2016
DOI: 10.1002/1873-3468.12160
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for inhibition of the deadenylase activity of human CNOT6L

Abstract: Human CNOT6L/CCR4, a member of the endonuclease-exonuclease-phosphatase (EEP) family enzymes, is one of the two deadenylase enzymes in the conserved CCR4-NOT complex. Here, we report inhibitor-bound crystal structures of the human CNOT6L nuclease domain in complex with the nucleotide CMP and the aminoglycoside neomycin. Deadenylase activity assays show that nucleotides are effective inhibitors of both CNOT6L and CNOT7, with AMP more effective than other nucleotides, and that neomycin is a weak deadenylase inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Small molecules that inhibit CAF1 deadenylase activity have recently been reported for human CAF1 Maryati et al, 2014Maryati et al, , 2015Zhang et al, 2016). Because these inhibitors are not commercially available, we have synthesized a series of pyrazolo[4,3-d]-pyrimidine and quinazoline derivatives with the purpose of finding novel CAF1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecules that inhibit CAF1 deadenylase activity have recently been reported for human CAF1 Maryati et al, 2014Maryati et al, , 2015Zhang et al, 2016). Because these inhibitors are not commercially available, we have synthesized a series of pyrazolo[4,3-d]-pyrimidine and quinazoline derivatives with the purpose of finding novel CAF1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest a model where the two aspartic residues (D287 and D346) are in close proximity in the reaction very dependent on the 3D conformation of the full enzyme that is absolutely essential to be conserved in order to coordinate the four catalytic residues in the exact optimal spatial positions in the proximity of the catalytic site of AtHESPERIN to achieve maximal efficacy. 3C) and may indicate the displacement of Mg 2+ from the active site could account for loss of activity as has been shown for CNOT6L (12).…”
Section: Accepted Articlementioning
confidence: 70%
“…DEDD nucleases are named after conserved Asp (D) and Glu (E) residues in their active site. EEP (exonuclease-endonuclease-phosphatase) nucleases have conserved catalytic Asp, Glu and His residues (5,10,11), which are important for Mg 2+ coordination and contribute to substrate positioning within the catalytic pocket (12).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of adenosine monophosphate (AMP) can inhibit deadenylation of the poly(A) tail for nuclear transcripts by potently inhibiting the major deadenylase CNOT6L and CNOT7 27 , leading us to ask whether the poly(A) tail length of MT-mRNAs was affected by adding AMP. Our results demonstrated that AMP addition did not affect the distribution of MT-mRNA in the poly(A) tail length in both mouse metaphase II (MII) oocytes and mouse 2-cell embryos (Fig.…”
Section: Resultsmentioning
confidence: 99%